Reconstruction of oral cavity defects using myogenous‐only scapular tip free‐flaps. Issue 4 (8th July 2022) - Barton, Blair M.; Pappa, Andrew K.; Blumberg, Jeffrey; Patel, Samip
Abstract: Background: Oral cavity reconstruction is very challenging anatomical subsite to reconstruct. Large defects often require free tissue reconstruction to provide the best chance of form and function. Additionally, free tissue reconstruction aids to prevent fistula formation. We aimed to determine outcomes of oral cavity defect reconstruction using scapular tip free flaps with a myogenous intraoral component. Methods: All patients with a mandibular or maxillary bony defect that included a disruption of the intraoral mucosa component between 07/1/14 and 07/31/17. Patients were reconstructed with a scapular tip free flap, which included a muscular component that was used to recreate the oral mucosa. The primary study outcomes were flap success rates, development of orocutaneous or oronasal fistula, rate of resuming oral diet as well as the occurrence of medical and surgical complications in the first month following surgery. The tested hypothesis was formulated before data collection began. Results: Twenty‐five patients were identified by the study criteria. There was one (4%) flap that failed, while orocutaneous fistula occurred in two patients (8%). Prior history of osteoradionecrosis was a statistically significant predictor of overall complication ( p  < .05). Conclusions: Intraoral myogenous reconstruction allows for re‐mucosalization of the oral cavity defect and is associated with high viability and low‐complication rates. In patients with amenable oral mucosal defects, a myogenous scapular tip free flap is a suitable reconstructive option. Abstract : The scapular tip flap with a chimeric muscle‐only component is a reliable source for re‐mucosalization of the oral cavity. This patient cohort demonstrates that free flap reconstructions based on the scapular tip offer a unique variability in terms of soft tissue reconstruction.